IN VIVO USE OF N-BUTYL-2-CYANOACRYLATE IN CLEFT PALATE SURGERY AND A COMPARISON OF ITS EFFICACY WITH SUTURE MATERIAL - Furkan Karabulut; Serhat Özbek (İstanbul Tıp Fakültesi Dergisi)
Objective: In this experimental work, we aimed to compare the efficacy of two different methods of combining the mucoperiosteal flaps in an animal model: using a tissue adhesive material N-butyl-2-cyanoacrylate (Glubran®2) and the classical suturing technique in cleft palate surgery. Methods: Rats were separated into group A and B. In group A (n=12) mucoperiosteal flaps were brought together with absorbable suturing material, while in group B (n=12), adhesive material was used for the same purpose. Palatal mucosa healing was evaluated histologically in terms of inflammatory cell infiltration, fibroblastic activity and vascularization on the postoperative 8th and 16th days. Results: As a result of this experimental study, there were no differences macroscopically in palatal mucosa healing in both groups. Histologically, on day 8, the inflammation severity was higher in the suture material group and the difference was statistically significant. On day 16, fibroblastic activity was significantly lower in the suture material group. There was no significant difference between the groups in terms of vascularity. Conclusion: As a result of these findings, Glubran®2 was found to be easily usable and effective with low complication rates, moreover, it was a practical tissue adhesive material for merging mucosal flaps in the midline of the palate.